2020
DOI: 10.1371/journal.pone.0229642
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration is associated with vitamin D deficiency in older women living in Macao, China: A pilot cross-sectional study

Abstract: Chinese women are known to have both a high prevalence of metabolic syndrome (MetS) and vitamin D deficiency (serum 25-hydroxyvitamin D (25OHD) <50 nmol/l). Associations between sleep duration and circulating 25OHD have recently been reported but, to our knowledge, these associations have not been studied in older Chinese populations. We thus investigated whether sleep duration was associated with vitamin D status in a population from Macao, China, and whether sleep duration modified the association between Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
(132 reference statements)
2
4
0
Order By: Relevance
“…Comparison with previous literature is complicated by the substantial variation in methodology, definition of outcomes and covariate adjustment across studies. A positive association between 25(OH)D and sleep duration, as found in some of our analyses, has been reported by others [ 15 , 16 , [18] , [19] , [20] , [21] , [22] , [23] ], although null findings have also been reported [ 40 , 41 ]. Moreover, a recent meta-analysis by Gao et al.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparison with previous literature is complicated by the substantial variation in methodology, definition of outcomes and covariate adjustment across studies. A positive association between 25(OH)D and sleep duration, as found in some of our analyses, has been reported by others [ 15 , 16 , [18] , [19] , [20] , [21] , [22] , [23] ], although null findings have also been reported [ 40 , 41 ]. Moreover, a recent meta-analysis by Gao et al.…”
Section: Discussionsupporting
confidence: 81%
“…Higher concentrations of serum 25-hydroxyvitamin D (s-25(OH)D), the main circulating vitamin D metabolite, have been associated with longer and earlier night sleep [ 15 ]. Moreover, vitamin D deficiency has been associated with short sleep duration [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ], poor self-reported sleep quality [ 24 , 25 ], and an increased risk of daytime sleepiness [ 26 , 27 ]. However, none of these previous studies have been performed in populations living in an Arctic area, in which the prevalence of both insufficient sleep duration and insomnia has been reported as worryingly high [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 In contrast to our findings, Liu et al found that both long and short sleep duration was associated with vitamin D deficiency in older Chinese women. 5 Almost same findings were found by Choi et al who stated that differences in log-transformed vitamin D status between the sleep insufficient or excessive sleep groups and the normal range sleep groups were not significant. 6 Though Abboud et al did systematic review and included 19 studies where they got the other way round and found that vitamin D status is promising in improving sleep quality.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, it has been proposed that vitamin D plays an important role in serotonin and melatonin regulation, which further indicates the relevance of vitamin D in mental health, especially the regulation of mood and sleep. 5 Vitamin D is an essential micronutrient during the growth and development of the human body, and 25hydroxyvitamin D [25(OH)D] is the most sensitive clinical marker for vitamin D status.…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have reported an association between vitamin D deficiency and poor sleep health, including increased risk of short sleep duration [ [24] , [25] , [26] ], daytime sleepiness [ 27 , 28 ] and poor sleep quality [ 29 , 30 ]. Nevertheless, a causal link has been difficult to demonstrate, as results from randomized controlled trials (RCTs) are scarce.…”
Section: Introductionmentioning
confidence: 99%